Wearable energy storage with MXene textile supercapacitors for real world use. Issue 7 (30th January 2023) - Inman, Alex; Hryhorchuk, Tetiana; Bi, Lingyi; Wang, Ruocun (John); Greenspan, Ben; Tabb, Taylor; Gallo, Eric M.; VahidMohammadi, Armin; Dion, Genevieve; Danielescu, Andreea; Gogotsi, Yury
Abstract : We demonstrate a Ti3 C2 T x MXene coated textile supercapacitor configured as five cells stacked in series with a high operating potential range of 6 V, capable of real time operation of a wireless sensor for over 90 minutes. Abstract : Successful implementation of wearable electronics requires practical wearable energy storage systems that can meet certain power and energy metrics. However, flexible, stretchable, and truly textile-grade energy storing platforms have so far remained missing from most e-textile systems due to the insufficient performance metrics of current available materials and technologies. Two-dimensional (2D) transition metal carbides and nitrides (MXenes) offer unique combinations of properties including metallic conductivity, high specific capacitance, hydrophilicity, and solution processability, as well as mechanical flexibility and robustness that render these materials promising for flexible wearable energy storage technologies. Here we demonstrate textile-based electrochemical capacitor devices with a high areal loading of Ti3 C2 T x that can be integrated in series via a stacked design approach and meet the real-world power requirements for wearable electronics. A demo textile supercapacitor with 5 cells in series, a footprint area of 25 cm 2 and an MXene loading of 24.2 mg cm −2 could operate in a 6 V voltage window delivering an energy density of 0.401 mW h cm −2 at a power density of 0.248 mW cm −2, and an areal capacitance of 146 mF cm −2 at a 0.16 mA cm −2 discharge current. The MXene textile supercapacitor powers a temperature monitoring system requiring high current densities with wireless data transmission to a receiver for 96 minutes. Power time is a crucial subject for integration of flexible supercapacitors with commercial microelectronics and successful commercialization of smart garments. This initial report of an MXene textile supercapacitor powering a practical peripheral electronics system demonstrates the potential of this family of 2D materials to support a wide range of devices such as motion trackers and biomedical monitors in a flexible textile form factor.